2017
DOI: 10.1289/ehp490
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition Analysis of Black–White Disparities in Birth Outcomes: The Relative Contribution of Air Pollution and Social Factors in California

Abstract: Background:Racial/ethnic disparities in preterm birth (PTB) are well documented in the epidemiological literature, but little is known about the relative contribution of different social and environmental determinants of such disparities in birth outcome. Furthermore, increased focus has recently turned toward modifiable aspects of the environment, including physical characteristics, such as neighborhood air pollution, to reduce disparities in birth outcomes.Objectives:To apply decomposition methods to underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 44 publications
1
37
1
1
Order By: Relevance
“…Racial and economic segregation may be better studied at more granular levels not available in national vital records. 20,46 Unlike other studies, this study demonstrated that the contribution of sociodemographic factors to the disparity in PTB may operate through more proximal maternal health characteristics. The findings show a sizable black −white disparity in hypertension during pregnancy, specifically chronic hypertension (Table 1).…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Racial and economic segregation may be better studied at more granular levels not available in national vital records. 20,46 Unlike other studies, this study demonstrated that the contribution of sociodemographic factors to the disparity in PTB may operate through more proximal maternal health characteristics. The findings show a sizable black −white disparity in hypertension during pregnancy, specifically chronic hypertension (Table 1).…”
Section: Discussioncontrasting
confidence: 80%
“…7 This reduction in explanatory power for VPTB is consistent with other analyses. 20,34 The study findings support the role of social determinants in driving a large portion of the black−white disparity in PTB and VPTB. The importance of education on health is well established, 35,36 and maternal education was found to be a meaningful contributor to PTB disparities in the present analyses.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In California, there are racial disparities in preterm birth; non-Hispanic black women have nearly double the prevalence of preterm birth of non-Hispanic white women (18). Despite calls in the environmental health literature (19), limited research has explored the modifying role of individual-level race/ethnicity and socioeconomic status in the relationship between air pollution and preterm birth (20)(21)(22), and none has done so in relation to point sources of pollution like power plants.…”
mentioning
confidence: 99%
“…Previous studies have focused on the sources of the Black-White disparity [2][3][4][5], which can be lower by virtue of high White versus low Black IMR [6], and limited in the provision of Black-specific contextual information as they are often dominated by the characteristics of the larger White community [5]. Studies that have examined Black infant mortality either alone or in addition to White infant mortality have suggested associations with various contextual factors within social, economic, environmental, and health domains but none have examined their contribution to regional variation [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Moreover, several studies have shown that the predictors of Black IMR are different than those of White IMR, and thus support a priority focus on the higher Black IMR [2,4,23,24].…”
Section: Introductionmentioning
confidence: 99%